2010
DOI: 10.1109/tbme.2010.2044178
|View full text |Cite
|
Sign up to set email alerts
|

Mass Customization of Foot Orthoses for Rheumatoid Arthritis Using Selective Laser Sintering

Abstract: Rheumatoid arthritis is an inflammatory joint disease that can lead to pain, stiffness, and deformity, often with marked involvement of the small joints of the foot and ankle. Orthotic devices are commonly prescribed for this condition to lessen symptoms and improve function and mobility, and customized devices are most effective. The work reported in this paper has examined the feasibility of using an additive manufacturing-based approach to manufacture customized orthoses. In order to test feasibility, ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 11 publications
1
95
0
1
Order By: Relevance
“…In literature, there is evidence to support the use of additive manufacturing for producing orthotic or prosthetic devices. [13][14][15][16][17][18][19] However, issues related to material properties and manufacturing costs still need to be investigated before additive technologies could be considered ready for clinical use. Furthermore, it is not clear to the authors how much evidence is necessary before one can consider these manufacturing technologies 'ready for commercial' use.…”
Section: Barefoot Gait (Sdmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there is evidence to support the use of additive manufacturing for producing orthotic or prosthetic devices. [13][14][15][16][17][18][19] However, issues related to material properties and manufacturing costs still need to be investigated before additive technologies could be considered ready for clinical use. Furthermore, it is not clear to the authors how much evidence is necessary before one can consider these manufacturing technologies 'ready for commercial' use.…”
Section: Barefoot Gait (Sdmentioning
confidence: 99%
“…12 Additive fabrication (selective laser sintering (SLS), in particular) has been recently proposed as a feasible engineering method for manufacturing of customized prosthetic feet, prosthetic sockets, customized foot orthoses and customized ankle-foot orthoses. [13][14][15][16] This technique allowed developing different manufacturing frameworks to replicate the shape and functional characteristics of existing carbonfibre AFO or to customize shape and functional AFO characteristics under a certain degree of automation. [17][18] Although the feasibility of the SLS manufacturing techniques for prosthetics and orthotics was demonstrated, studies on the safety, comfort and effectiveness of SLS orthotics are only nowadays being considered.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the cost effectiveness of providing foot orthoses in the UK National Health Service (NHS) has been raised in chronic musculoskeletal foot conditions [14], as it represents a considerable burden to patients, clinicians and health providers. However, data relating to costeffectiveness of the use of foot orthoses for people with RA are limited [15][16][17]. One UK study reported that foot orthoses should be replaced every 24 months, incurring low annual treatment costs as the FO unit used in the study cost £60 per pair [15].…”
Section: Introductionmentioning
confidence: 99%
“…One UK study reported that foot orthoses should be replaced every 24 months, incurring low annual treatment costs as the FO unit used in the study cost £60 per pair [15]. In another UK study, Pallari [16] reported that RA patients paid on average £50 for customised foot orthoses using a digital threedimensional laser scanner. With such limited data the aim of this study was to evaluate the clinical and cost effectiveness of custom-made foot orthoses compared to simple insoles when prescribed for people with established RA.…”
Section: Introductionmentioning
confidence: 99%
“…Once the virtual mask is modelled, it may be manufactured by using any AM technology that has been previously used in a number of medical applications, including design and manufacturing of medical splints for ankle-foot (Pallari et al 2010) (Faustini et al 2008;Mavroidis et al 2011) or wrist (Palousek et al 2014;Paterson 2013). The physical prototype can be later post-processed for particular applications with conventional existing techniques, such as metal spraying for patientspecific face masks necessary for radiography applications in cancer treatment (Deon J. de Beer et al 2005).…”
Section: Introductionmentioning
confidence: 99%